Evaluación de tres productos de síntesis biológica para el control de oídio (Sphaerotheca pannosa) en el cultivo de rosas (Rosa sp.), var. Gotcha, en el cantón Pedro Moncayo, provincia de Pichincha 2021 - Cumbal Collaguaso, Blanca Alicia (2021)
This research was carried out at the Miltflowers farm located in the Ñañoloma community, Tupigachi Parish, Pedro Moncayo Canton, Pichincha Province, where three biological synthesis products were evaluated for the control of powdery mildew (Sphaerotheca pannosa) in the cultivation of roses (Rosa sp.) variety Gotcha. The experimentation was managed through a Completely Random Block Design (DBCA) with factorial arrangement A x B + 1, with 10 treatments and three repetitions, giving a total of 30 experimental units; The biological synthesis products evaluated were: Trichoderma spp., Bacillus spp., Melaleuca alternifolia, with three doses each, compared to the Control (without application). The variables evaluated were: incidence, severity at 0 days (before application) and at 7, 14, 21, 28 days after application; persistence was evaluated in the weeks after the last application. The data were subjected to the analysis of variance (ADEVA), and the comparison of treatments was carried out with the Tukey test at 5%. In the control of powdery mildew (Sphaerotheca pannosa) in the Gotcha variety, the Trichoderma spp. in doses of 6 cc / l and Bacillus spp. In doses of 3 cc / l, through those were obtained the lowest percentage of incidence, severity and persistence of the disease and also due to the evident effectiveness of control, they registered a lower economic cost of $ 544.00 and $ 320.00 USD / ha / month correspondently. Concluding that the use of biological synthesis products is a viable alternative in the control of the disease.